2021
DOI: 10.3390/w13243522
|View full text |Cite
|
Sign up to set email alerts
|

Organic Pollutants Removal from Olive Mill Wastewater Using Electrocoagulation Process via Central Composite Design (CCD)

Abstract: Electrocoagulation (EC) was studied in this study as a potential alternative approach for treating Olive Mill Wastewater (OMW). Aluminum plates were utilized as anode and cathode to evaluate the removal of Chemical Oxygen Demand (COD) from OMW and the aluminum electrode’s weight loss. Central Composite Experimental Design (CCD) and Response Surface Methodology were used to optimize its performance. Anodes were weighed before and after each electrocoagulation experiment, to compare the experimental and the theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These removal rates were 88%, 68%, and 33% for the Al electrode, respectively [37]. It has been reported that the performance of electrocoagulation to treat wastewater containing micellar surfactant is influenced by several factors such as surfactant initial concentration, reactor polarity, current density, electrode material (e.g., Al or Fe), and processing time [38].…”
Section: Electrocoagulationmentioning
confidence: 94%
“…These removal rates were 88%, 68%, and 33% for the Al electrode, respectively [37]. It has been reported that the performance of electrocoagulation to treat wastewater containing micellar surfactant is influenced by several factors such as surfactant initial concentration, reactor polarity, current density, electrode material (e.g., Al or Fe), and processing time [38].…”
Section: Electrocoagulationmentioning
confidence: 94%
“…h.m −3 for the 7400 mg/L with the application of an electrical potential of 3, 5, 7, and 9 V. The results indicated that the increase in the electrical potential applied to the electrocoagulation cell significantly affects the energy consumption, as clearly shown in Figure 7. In previous studies, it was observed that the energy consumption increases markedly when a higher electrical potential is applied to the electrocoagulation cell [46]. The energy consumption increases with the intensity of electric current, and the applied potential due to the increase of polarization in the electrodes.…”
Section: Enenergy Consumption Analysismentioning
confidence: 96%